Metabolic and psychological responses of women endurance runners to high volume training - Sims, S. T.; Brewer, B.; Berger, J.; Headley, S. A. (Medicine & Science in Sports & Exercise, 1998)
The metabolic and psychological responses of women to a 7-day high-volume running program were assessed. Endurance runners were assigned to a control (N = 6) or high-volume (overreached; N = 7) group. Baseline mileage was maintained for two weeks before the experimental intervention. Increasing training volume by 40% stimulated overreaching. The control group did not change in any of the measured variables. The overreached group exhibited decreases in maximal lactate concentrations, increases in total mood disturbance, and decreases in plasma glutamine concentrations. Implication. Sudden increases in training demands of female distance runners alter lactate mechanisms and negatively affect immunological and psychological functioning.